Autoencoder based underwater wireless optical communication with high data rate - Zou, Cong; Yang, Fang (Optics letters, 2021)
Underwater wireless optical communication (UWOC) has great potential to provide higher data rates and lower time delay communication compared to radio frequency and acoustic counterparts. However, UWOC systems with wide bandwidths are subject to photon absorption and scattering, which result in severe energy loss for optical beams and inter-symbol interference. To overcome these issues, this Letter interprets the UWOC system as an autoencoder (AE), named UWOC-AE, which takes advantage of the double Gamma function approximating channel impulse response of underwater optical links to learn the channel characteristics. Thus, within the AE framework, the encoder and decoder can be optimized jointly. Experiments indicate that the proposed UWOC-AE can achieve superior performance with high data rates compared to existing techniques.